2000
DOI: 10.1253/jcj.64.156
|View full text |Cite
|
Sign up to set email alerts
|

Ampulla Cardiomyopathy(‘Takotusbo’ Cardiomyopathy)

Abstract: The clinicopathologic findings of reversible ampulla-like ventriculogram of the left ventricle were studied in 8 elderly women and one middle-aged man. Their coronary arteriograms were normal, even in the 7 patients who had ST elevation on electrocardiogram. Coronary spasm was positive in only 2 of the 7 patients who received provocation tests. Biopsy specimens revealed focal myocyte injury. Normal coronary arteriograms during ST elevation and the presence of pathologic myocardial lesions were not consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(40 citation statements)
references
References 8 publications
1
38
0
1
Order By: Relevance
“…TT cardiomyopathy is characterized by transient LV dysfunction with chest symptoms and ECG changes that mimic those of acute myocardial infarction in patients with normal findings on coronary angiography [3]. TT cardiomyopathy alone has not yet been explained, and it is speculated to be induced by emotional or physical stress [4].…”
Section: Discussionmentioning
confidence: 99%
“…TT cardiomyopathy is characterized by transient LV dysfunction with chest symptoms and ECG changes that mimic those of acute myocardial infarction in patients with normal findings on coronary angiography [3]. TT cardiomyopathy alone has not yet been explained, and it is speculated to be induced by emotional or physical stress [4].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the triggering factors, a preceding acute medical condition induced TCM in 43% of cases and emotional factors in the remaining cases [2]. Our case series illustrates the very heterogeneous nature of the clinical presentations, triggering factors and outcomes severity in TCM.…”
Section: Discussionmentioning
confidence: 71%
“…It was first described in Japan and it was named Takotsubo cardiomyopathy (TCM) because of the resemblance between the left ventricular appearance in systole and the shape of a pot with a round bottom and a narrow neck (Takotsubo = Japanese octopus trap) [2,3]. This syndrome is characterized by acute LV dysfunction with regional wall motion abnormalities (WMA) extended beyond a single coronary vascular bed, absence of significant obstructive coronary obstructive disease, and rapid improvement of LV function within a few days or weeks [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, two reports of myocardial biopsy in the setting of transient left ventricular dyskinesis resembling LVABS have been published. In both, the authors found focal myocyte injury which is not consistent with the concept of stunning [21,26]. Transient ischemic episodes due to epicardial coronary artery occlusion from spasm or thrombosis may lead to stunned myocardium or reperfusion injury.…”
Section: Stunned Myocardium and Apical Ballooningmentioning
confidence: 77%